2005
DOI: 10.1097/01.mcg.0000177257.87939.00
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Mortality in Acute Pancreatitis

Abstract: Severe acture pancreatitis (SAP), a multisystem disease, is characterized by multiple organ system failure and additionally by local pancreatic complications such as necrosis, abscess, or pseudocyst. The rate of mortality in SAP, which is about 20% of all cases of acute pancreatitis (AP), may be as high as 25%, as in infected pancreatic necrosis. The factors that influence mortality in different degrees are various. Etiology for the episode, age, sex, race, ethnicity, genetic makeup, severity on admission, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 141 publications
(115 reference statements)
2
49
0
4
Order By: Relevance
“…We also observed significant improvement in Marshall score and MODS of patients with resolution of IAH. The overall mortality rate in our study of approximately 23% is comparable to the 10%-50% reported in AP patients by others [18][19][20][21] . The mortality in ACS patients in our study (75%), however, was much higher than that in patients without ACS which is not acceptable for us, although post-injury ACS has been consistently reported to have a high mortality ranging from 25%-75%.…”
Section: Discussionsupporting
confidence: 76%
“…We also observed significant improvement in Marshall score and MODS of patients with resolution of IAH. The overall mortality rate in our study of approximately 23% is comparable to the 10%-50% reported in AP patients by others [18][19][20][21] . The mortality in ACS patients in our study (75%), however, was much higher than that in patients without ACS which is not acceptable for us, although post-injury ACS has been consistently reported to have a high mortality ranging from 25%-75%.…”
Section: Discussionsupporting
confidence: 76%
“…(14) There are many causes but the most important so far are considered to be gallstones and alcohol. (15)(16)(17)(18) It has been claimed that gallstone of small size up to 5mm can enter the cystic duct and can produce this lethal syndrome. (19) There is a global consensus that female are the common victims as they harbor gallstones more frequently than males and males are more frequent victims because of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…In elderly patients, the biliary and idiopathic pancreatitis are reported as 64.9% and 26.6% respectively (22). Many studies have indicated a worse prognosis in idiopathic AP compared to pancreatitis induced by alcoholism or gallstone (23).…”
Section: Discussionmentioning
confidence: 99%